Economic and Spatial Study of the Vulnerability and Adaptation to Climate Change of Coastal Areas in Senegal - World Bank (Washington, DC, 2014)
The African coastal countries are facing several environmental and socio-economic challenges, such as unplanned urban and economic development, fueled by a growing rural exodus; non-functional or non-existent public infrastructures to handle the demographic growth along the coastline; air, water and soil pollution; and alteration of coastal ecosystems. West Africa, in particular, is facing severe land losses and major damage due to coastal erosion and shoreline loss. This situation impacts coastal communities, infrastructures and users, and hampers economic growth. The institutional, technical and financial capabilities at the regional, national and local scales are not sufficient to effectively meet these challenges. The impacts of climate change intensify these trends and induce accelerated coastal erosion, loss of land and assets, river or run-off floods, marine submersion, groundwater salinization and changes in the distribution and abundance of coastal and marine habitats and species. The World Bank, supported by the governments of Norway and Finland, assists the Senegalese government in developing reforms program, in improving the country's technical and financial adaptability and in integrating climate resilience into the future development plans regarding the coastline of Senegal. The aim of this study is to carry out a spatial and economic analysis of the coastal areas' vulnerability to climate change and natural risks in Senegal, and to perform an economic analysis of different adaptation options in three pilot sites.